Observing early stage rail axle bearing damage. (October 2015) - Symonds, N.; Corni, I.; Wood, R.J.K.; Wasenczuk, A.; Vincent, D.
Highlights: On-board vibration sensors are correctly identifying failing rail axle bearings. Damaged bearings removed from trains are being examined, and measured. CT has been used to identify and locate subsurface bearing damage. Premature rolling contact fatigue (RCF) of the stationary outer ring has been confirmed. Large white etched layers have been observed. Abstract: Rail axle-bearing failure is a serious issue that can affect passenger safety and generate large costs for operators from penalties, recovery, reduced train availability and repairs. Southeastern have fitted bearing sensors to their Electrostar fleet; these sensors identify rail axle-bearing degradation. In this paper (presented at ICEFA VI) we introduce an on-going study where ex-situ rail axle bearings with recorded vibration histories are being forensically examined. The ultimate aims of this work are (1) to link vibration signatures to levels of physical damage and (2) to identify any common factors that are causing bearing failures. The current work presents results from one removed bearing; this work highlights the methods and techniques being used to measure and quantify the physical damage, which include profilometry, X-ray tomography and metallography. The bearing described herein presented large subsurface white etched layers, rolling contact fatigue crack propagation and evidence of electrical arcing damage.